Penerapan Komunikasi dan Edukasi pada Kegiatan Pengolahan Tofu Pudding dan Tofu Milkshake - Esteria Priyanti; Maeva Ristianti Fatharani Putri; Nur Rahito; Lucia Rasifa Anggira; Bagaskara Agung Putra Wicaksono; Felicia Ananda Putri (ABDI KARYA : Pengabdian Kepada Masyarakat, 2025)
Activity for implementing communication and education in the processing of tofu pudding and tofu milkshake are integrated into Business Communication subject and Community Service for students. The success of this activity is assessed through 2 indicators, which are the assessment of the lecturer teaching the Business Communication subject to the training organizing committee and the assessment of participant satisfaction to the committee who has organized this training. The indicator of success for implementing this training is that the committee can master several competencies from the Business Communication subject. Through this training, it is also hoped that participants who take part in this training will gain new education and experience in processing tofu pudding and tofu milkshakes. This activity was attended by 9 participants and was carried out using educational lecture methods and practice in processing tofu pudding and tofu milkshake. As a result of this activity, it can be concluded that the training organizing committee has been able and successful in organizing training using communication principles, and all participants can process tofu pudding and tofu milkshake according to the expected criteria.